COMBINING PRODUCT AND PROCESS BASED APPROACHES TO TEACHING WRITING DISCUSSION TEXTS - Agustiana, Vina (2015)
Combining product and process based approaches appears to be worthy of investigation since it has its own strengths and weaknessess. The present study examines the activities of teaching-learning writing discussion texts when product and process based approach combination is implemented in EFL writing classroom, the effects of applying the product and process based approach combination on EFL students' writing skill, and the students' attitude toward the implementation of product and process based approach combination in the classroom. This study used a mixed-methods research through applying an embedded design. This study involved 24 second grade students of a private university in West Java, Indonesia. There were four instruments used, namely field notes, videotapes, students' test (pre-test and post-test), and questionnaires. Data taken from field notes and videotapes were analyzed qualitatively to examine the activities of the teaching-learning writing discussion texts when the product and process based approach combination was implemented in the classroom. Data taken from the students' tests were analyzed statistically and qualitatively to examine the improvement in the students' writing skill. Data taken from questionnaire was analyzed by descriptive statistics to examine the students' attitude toward the implementation of product and process based approach combination. The findings show that the students were actively involved in class when the teacher applied the product and process based approach combination in writing classroom. There was also the improvement in the students' writing skill based on the result taken from the students' pre-test and post-test since the level of significance (two-tailed) in paired t-test is less than the alpha (0.000<0.05). Qualitatively, the improvements were also found in generic features, textual language, and syntactical language aspects. In addition, the students showed highly positive attitude (4.35 average score) toward the implementation of the approach in the classroom. The methodological and practical suggestions are also presented. Mengkombinasikan pendekatan produk dan proses dalam pengajaran menulis merupakan hal yang menarik untuk diteliti, mengingat kedua pendekatan menulis tersebut memiliki kelemahan dan kekurangannya masing-masing. Penelitian ini bertujuan untuk mengidentifikasi proses kegiatan belajar-mengajar menulis teks diskusi ketika kombinasi pendekatan produk dan proses diterapkan di kelas menulis, efek penerapan kombinasi pendekatan produk dan proses terhadap kemampuan menulis siswa, dan perilaku siswa terhadap penerapan kombinasi pendekatan produk dan proses di dalam kelas menulis. Penelitian ini menggunakan penelitian campuran dengan menerapkan "embedded design". 24 orang mahasiswa tingkat dua yang berasal dari universitas swasta di Jawa Barat, Indonesia, menjadi responden pada penelitian ini. Terdapat empat instrumen yang digunakan, yaitu catatan lapangan, video, hasil tes siswa (pre dan post), dan kuesioner. Data yang berasal dari catatan lapangan dan video dianalisa secara kualitatif untuk mengidentifikasi proses kegiatan belajar-mengajar menulis teks diskusi ketika kombinasi pendekatan produk dan proses diterapkan di kelas menulis. Data yang berasal dari hasil tes siswa dianalisa secara statistik dan kualitatif untuk mengidentifikasi efek penerapan kombinasi pendekatan produk dan proses terhadap kemampuan menulis siswa. Data yang berasal dari kuesioner dianalisa secara statistik deskriptif untuk mengidentifikasi perilaku siswa terhadap penerapan kombinasi pendekatan produk dan proses di dalam kelas menulis. Hasil penelitian menunjukkan bahwa siswa aktif dalam kelas menulis ketika guru menerapkan kombinasi pendekatan produk dan proses. Selain itu, terdapat peningkatan kemampuan menulis siswa berdasarkan hasil tes menulis siswa, dimana signifikan level (two-tailed) dalam "paired t-test" lebih kecil dari alpha (0.000<0.05). Secara kualitatif, peningkatan kemampuan menulis siswa juga terlihat dari beberapa aspek menulis, yaitu generic features, textual language, and syntactical language aspects. Selain itu, siswa menunjukkan perilaku positif yang tinggi terhadap penerapan kombinasi pendekatan produk dan proses dalam kelas menulis.